Therapeutic devices for epilepsy - Fisher, Robert (Henry Stewart Talks, 2011)
Epilepsy, Seizures, Medically refractory seizures, Vagus nerve stimulation, Seizure detection, Seizure prediction, Cortical cooling, Optogenetics, Brain perfusion, Intracerebroventricular therapy, Transcranial magnetic stimulation, Deep brain stimulation, Update interview: Responsive neurostimulation
Updated at 2021/02/20